THE COMPETITIVENESS OF HOTEL FACILITIES. THEORY AND PRACTICE - KOBYAK, Marina Viktorovna; LVOVNA, Ilina Elena (Journal of Environmental Management and Tourism, 2016)
The present stage of economic development in Russia is characterised by the intensive growth of its market, the introduction and rapid expansion of new forms of competitive relations. Firstly, the competition for natural resources and goods has been replaced by the competition for customers. Secondly, stable social and economic relations have not been formed in hotel business yet. These two factors have determined the development of tourism. At the present time hotel business is among leaders within the service sector which greatly influences the major branches of economy: transportation, communication, construction, agriculture, the production of fast moving consumer goods etc. The supply of hotel services is boosting while rates of growth for this sector reaches 20% per year. This article is concerned with the authors’ methodology for evaluating the efficiency of hotel facilities which enables them to apply a specific evaluation approach in accordance with the following classification criteria: the specialisation of lodging facilities, a hotel type, its rating or category, room capacity, location, average residence. Furthermore, the authors have developed the matrix of the weight indices for profit centres within lodging facilities regarding all essential features.
Keywords: Hotel facility; efficiency; service; lodging facilities, hotel room capacity; profit centers; weight indices